16S metagenomics for diagnosis of bloodstream infections: opportunities and pitfalls. (3rd August 2018) - Rutanga, Jean Pierre; Van Puyvelde, Sandra; Heroes, Anne-Sophie; Muvunyi, Claude Mambo; Jacobs, Jan; Deborggraeve, Stijn
ABSTRACT: Introduction : Bacterial bloodstream infections (BSI) form a large public health threat worldwide. Current routine diagnosis is based on blood culture (BC) but this technique suffers from limited sensitivity. Molecular diagnostic tools have been developed for identification of bacteria in the blood of BSI patients. 16S metagenomics is an open-ended technique that can detect simultaneously all bacteria in a given sample based on PCR amplification of the 16S ribosomal RNA gene (rDNA) followed by sequencing of the PCR amplicons and taxonomic labeling of the sequence reads at genus or species level. Areas covered : Here we review the studies that have used 16S metagenomics for the identification of bacteria in human blood samples. We also discuss the potential added value of 16S metagenomics in the diagnosis of BSI, challenges as well as future directions for implementation in clinical settings. Expert commentary : 16S metagenomics has the potential to complement conventional BC; however, the technique currently suffers from several technical limitations jeopardizing implementation in routine clinical microbiology laboratories. Further studies are required to assess the cost-efficiency and clinical impact of 16S metagenomics in comparison to BC which remains the gold standard diagnostic method for BSI.